Research on Submarine Magnetic Field Simulation with Energized Coil - Feng GUAN; Zhaohua SHENG (水下无人系统学报)
Due to the obvious advantages of high fidelity, adjustable magnetic field distribution and intensity, good maneuverability, low environmental dependence, and high safety of submarine magnetic field, the method of concentric magnetic field with energized coil has attracted more and more attention. It is necessary to conduct in-depth research on the distribution characteristics of the submarine magnetic field simulator with energized coil, so as to better guide its design. In this paper, the calculation methods of the spatial magnetic field of the submarine and the spatial magnetic field of arbitrary energized wire were given, and the submarine magnetic field simulation engineering scheme of the split-type three-axis orthogonal coil was proposed. The spatial magnetic field distribution characteristics of this scheme and the submarine were compared. The results show that the three-axis orthogonal coil method can simulate the spatial magnetic field distribution characteristics of a submarine well but cannot fully reflect the distribution scale, providing technical reference for submarine magnetic field simulation.